Patient prioritization of comorbid chronic conditions in the Veteran population: Implications for patient-centered care. (25th November 2016) - Richardson, Lorilei M; Hill, Jennifer N; Smith, Bridget M; Bauer, Erica; Weaver, Frances M; Gordon, Howard S; Stroupe, Kevin T; Hogan, Timothy P
Objective: Patients with comorbid chronic conditions may prioritize some conditions over others; however, our understanding of factors influencing those prioritizations is limited. In this study, we sought to identify and elaborate a range of factors that influence how and why patients with comorbid chronic conditions prioritize their conditions. Methods: We conducted semi-structured, one-on-one interviews with 33 patients with comorbidities recruited from a single Veterans Health Administration Medical Center. Findings: The diverse factors influencing condition prioritization reflected three overarching themes: (1) the perceived role of a condition in the body, (2) self-management tasks, and (3) pain. In addition to these themes, participants described the rankings that they believed their healthcare providers would assign to their conditions as an influencing factor, although few reported having shared their priorities or explicitly talking with providers about the importance of their conditions. Conclusion: Studies that advance understanding of how and why patients prioritize their various conditions are essential to providing care that is patient-centered, reflecting what matters most to the individual while improving their health. This analysis informs guideline development efforts for the care of patients with comorbid chronic conditions as well as the creation of tools to promote patient–provider communication regarding the importance placed on different conditions.